ANALISIS PENGARUH UPAH MINIMUM PROVINSI (UMP), INVESTASI TERHADAP PENYERAPAN TENAGA KERJA DI PROVINSI JAWA TENGAH TAHUN 2007-2017 - Rieky Hermawan; Lucia Rita Indrawati; Sudati Nur Sarfiah (DINAMIC : Directory Journal of Economic, 2019)
This study aims to determine: (1) the effect of provincial minimum wages on employment in Central Java Province in 2007-2017, (2) the effect of investment on employment in Central Java Province in 2007-2017, (3) the effect of minimum wages province, investment in employment in Central Java Province 2007-2017. The method of data analysis uses the Classical Assumption Test, Multiple Linear Regression Analysis, Statistical Test consisting of statistical t test, statistical F test, and Determination Coefficient Test (R2). The results of the study indicate: (1) there is a positive and meaningful influence of the provincial minimum wage on employment in Central Java Province in 2007-2017, (2) there is a positive and meaningful influence of investment in employment absorption in Central Java Province in 2007- 2017, (3) there is a significant and significant effect of provincial minimum wages, joint investment in employment in Central Java Province 2007-2017.